Two new species of Saussurea (Asteraceae, Cardueae) from Xinjiang, China - Du, Si-Yi; Li, Tian; Xu, Lian-Sheng; Chen, You-Sheng (Phytotaxa, 2025)
Two new species of Saussurea (Asteraceae, Cardueae) from Xinjiang are described and illustrated herein. Saussurea aksuensis differs from S. karaartscha in having numerous capitula and smaller involucres. Saussurea tianshanensis is morphologically distinguished from S. yabulaiensis by typically pinnately divided leaves with arachnoid hairs on the surface, and by having fewer phyllaries. It further differs from S. mae by its higher stems and purplish-green phyllaries. Molecular phylogenetic results based on Hyb-Seq data indicates that these populations are new species belonging to S. subg. Theodorea.